A Japanese Kampo Herbal Medicine Reduces the Severity of Inflammatory Bowel Disease - Cock, Ian E (Pharmacognosy Communications)
Duiakenchuto (DKT) is one of the most commonly used herbal remedies in Japanese Kampo medicine, particularly for digestive complaints.1,2 It is a poly-herbal preparation, which consists of Ginseng radix (commonly known as ginseng), Zanthyoxylum fructus (Japanese pepper) and Zingiberis siccatum rhizome (ginger), mixed with maltose powder. Despite its common usage, rigorous scientific evaluations of its effects are lacking.